Pandora’s Tongues - Littau, Karin (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractPandora's Tongues — This paper looks at translation not from the perspective of Babel, the "male god" as Jacques Derrida and George Steiner do, but from the perspective of Pandora, the first woman of the Greek creation myth, in order to offer a feminized version of the primal scattering of languages. The aim is to pose through the figure of Pandora questions about language and woman, and by extension, the mother tongue and female sexuality. Whilst the myth of the tower of Babel makes visible the filiations of translation and the word of the Father, the myth of Pandora allows us to uncover the matrix between translation and the mother tongue, presents us, in other words, with new possibilities for translation and gender.